Exploring the Role of Belongingness in Shaping Social and Personal Relationships - Zhepei Xuan; Monica Carr (Developmental and Clinical Psychology, 2025)
Belongingness, as a core psychological need, significantly influences an individual’s emotional well-being and social/ personal relationship satisfaction. This need holds substantial importance in interpersonal relationships and social dynamics, rooted in Maslow’s hierarchy of needs and Leary’s belongingness hypothesis (Baumeister & Leary, 1995; Maslow, 1943). This study employs a quantitative research approach using survey methodology to examine the links between belongingness, social and personal support, and self‑esteem. The primary objective is to provide empirical data that enhances psychological models of belongingness, ultimately guiding future interventions to foster inclusivity and support within social and interpersonal relationships. Given the existing gap in quantitative research on belongingness, this study contributes valuable empirical insights into the field. In light of increasing social isolation and weakened interpersonal connections in recent years, understanding how belongingness influences individual well-being is both timely and relevant. By investigating the impact of belongingness, this study aims to offer a data-driven perspective to social psychology.